Centenarians' Autobiographies : Age, Life Writing and the Enigma of Extreme Longevity - Banerjee, Mita (2024)
Situated at the intersection between medical humanities, aging studies, autobiographical studies, disability studies and ethic studies, this book explores the fascination of centenarians' autobiographies for humanites research. It can be argued that the growing presence of centenarians' autobiographies on book markets across the globe may by rooted in the public's desire for positive images of aging, in contrast to the image of inevitable decay.